ESTIMASI POTENSI PRODUKSI IKAN DI DANAU SINGKARAK SUMATERA BARAT BERDASARKAN NILAI KLOROFIL-A DAN KELIMPAHAN FITOPLANKTON - Sarifah Aini; Dinno Sudino; Angkasa Putra; Yenni Nuraini; Mira Maulita; Nabila Rizqiah Ramadhanty; Hamdani Hamdani; Deni Aulia; Herianto Suriadin (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2023)
The diversity of fish in marine waters is more than in lakes. However, the lake also has high fishery potential, one of which is Singkarak Lake, Solok Regency. On the island of Sumatra, the first largest lake is Lake Toba, while the second is Lake Singkarak. On the one hand, there are several human activities around the lake that cause a decrease in the production of fish catches, such as fishermen who often catch fish with tools that are not environmentally friendly, are not selective and lead to overfishing. Therefore, the purpose of this research is to examine the potential for fish production in Lake Singkarak based on the value of chlorophyll-a and abundance of phytoplankton. The method used is a survey method. The data analysis process includes analysis of fish production potential on the value of chlorophyll-a and analysis of fish production potential on phytoplankton abundance. Based on the chlorophyll-a value, the estimated fish production potential in Singkarak Lake is 4,663 tons/year and based on the abundance of phytoplankton, the fish production potential is 21,852 tons/year.